Eco-renaissance in floriculture: unlocking the power of plant growth-promoting bacteria - Mohamed Asik M; C Subesh Ranjith Kumar; P Irene Vethamoni; U Sivakumar; R Jagadeeswaran; M. Djanaguiraman (Plant Science Today, 2024)
The conventional floriculture industry heavily relies on chemical fertilizers and pesticides to meet global demand, which can have detrimental environmental impacts. To promote sustainable flower cultivation, Plant Growth-Promoting Bacteria (PGPB) has emerged as eco-friendly tools to enhance the productivity of major commercial flower crops. This review summarizes the current knowledge on diverse PGPB genera associated with ornamentals like rose, gerbera, carnation, chrysanthemum and orchids. It examines the abilities of PGPB to improve yield, quality and stress tolerance of flowers through mechanisms such as biological nitrogen fixation, nutrient solubilization, phytohormone synthesis, induced systemic resistance and antagonism against pathogens. The potential of developing microbial consortia and bioformulations as PGPB-based biofertilizers, bio stimulants and biopesticides for sustainable floriculture is discussed. By identifying research gaps and prospects, this review highlights the role of PGPB in driving sustainable intensification of commercial flower production with reduced environmental footprint.